Hukum Zakat dan Filosofinya Sebagai Instrumen Kemakmuran Umat - M. Ali Mansyur (Jurnal Hukum, 2014)
AbstractZakat Law is an instrument of prosperity of the people, if the principle of normative religious charity can be understood and implemented in life through understanding, practice and efficient distribution, then ideals to reduce or eradicate poverty through zakat will be realized. Reality shows the awareness of paying zakat remains low, which is considered as a liability zakat only the individual, so it does not considered as personal responsibility. Efforts to raise awareness of Muslims to pay zakat is very important and needs to be pursued through a variety of ways including: providing an understanding, make a breakthrough improvement in the economy of the people, professional management, transparency, encouraging people to tithe and the example of leaders who set an example by people with no intention of riya or show off. It is no less important thing to grow the awareness law of people to change and optimally utilize our potential, changing from mustahiq become the muzakki.Keywords: Zakat Law, the prosperity of the people, and self-awareness law of paying zakat. AbstrakHukum zakat merupakan instrumen kemakmuran umat, jika prinsip – prinsip zakat yang bersifat normatif agamis dapat dipahami dengan baik dan diimplementasikan dalam kehidupan melalui pemahaman, pengamalan dan pentasyarufannya, maka cita – cita mengurangi atau memberantas kemiskinan melalui zakat akan terwujud. Realitas menunjukkan kesadaran hukum masyarakat muslim membayar zakat masih rendah, hal mana karena menganggap zakat hanya sebagai kewajiban yang bersifat individual, sehingga tidak membayar zakat dianggap tanggung jawab pribadi.  Upaya menumbuhkan kesadaran muslim untuk membayar zakat sangat penting dan perlu ditempuh melalui berbagai cara diantaranya: memberikan pemahaman, membuat terobosan perbaikan ekonomi umat, profesionalisme pengelolaan, transparansi, membangkitkan semangat umat untuk berzakat dan keteladanan dari tokoh – tokoh umat yang menjadi panutan dengan tanpa bermaksud riya atau pamer. Hal yang tidak kalah penting lagi adalah menumbuhkan kesadaran hukum umat untuk berubah dan mendayagunakan potensi diri secara optimal, berubah dari mustahiq menjadi muzakki.Kata kunci: Hukum Zakat, kemakmuran umat, dan kesadaran hukum umat untuk berzakat.